Verification templates for the analysis of user interface software design - Harrison, Michael douglas (2019)
The paper describes templates for model-based analysis of usability and safety aspects of user interface software design. The templates crystallize general usability principles commonly addressed in user-centred safety requirements, such as the ability to undo user actions, the visibility of operational modes, and the predictability of user interface behavior. These requirements have standard forms across different application domains, and can be instantiated as properties of specific devices. The modeling and analysis process is carried out using the Prototype Verification System (PVS), and is further facilitated by structuring the specification of the device using a format that is designed to be generic across interactive systems. A concrete case study based on a commercial infusion pump is used to illustrate the approach. A detailed presentation of the automated verification process using PVS shows how failed proof attempts provide precise information about problematic user interface software features.